CFD INVESTIGATION OF THE EFFECT OF MODIFIED TWISTED TAPE ON HYDROTHERMAL ENHANCEMENT IN VERTICAL PIPE - Alnasur, Fawzi Sh.; Alturaihi, Riyadh S. (Journal of Applied Engineering Science, 2024)
Heat transfer enhancement has been a significant focus in hydrothermal engineering for several decades. The current paper represents an investigation using computational fluid dynamics (CFD) for a vertical circular tube having twisted taper inserted (plain and modified) with different twisted tape ratios TR, i.e., 7.8, 3.9, and 2.6, at three uniform wall heat fluxes and ranges of Reynolds number as boundary conditions. The twisted strips were used as a system to produce a turbulent, powerful swirl flow with an increase in the intensity of the secondary flow at the radial direction of the tube. The (friction facto) f and (Nusselt number) Nu were two measures of pressure loss and heat transfer variation that have been studied and graphically depicted. So, to balance the heat transfer enhancement quantity with pressure losses, the performance evaluation factor PEF was tested. It was observed that the twisted tape insert enhances the radial secondary flow intensity. The findings demonstrated that, in every scenario, the increase in(Reynold number)Re at the inlet, heat flux quantity, and twisted ratio results from a proportionate increase in heat transfer. At the same time, the friction factor decreases with an increase in all boundary conditions, except the twisted ratio, where the friction factor increases with increasing heat transfer. After accounting for heat transfer and friction coefficient, it was discovered that the tube with modified twisted stripe and the twist ratio was 3.9 performs best out of all the configurations examined. The performance evaluation factor PEF of pipes inserted with modified twisted tape was higher, reaching 1.5. This study is based on enhancing a high-performance evaluation factor of heat exchangers for use in industrial settings.
Keywords: twisted tape, swirling flow, performance evaluation factor